Analysis of Occupational Safety and Health (K3) Risk Management in the Physics and Chemistry Laboratory of the Medan Occupational Safety and Health Center - Irza Menka Deviliany Kaban; Razia Begum Suroyo; Tri Niswati Utami (International Journal of Public Health, 2024)
The many possible risks associated with laboratory work are unavoidable. This study aimed to determine and analyze hazards, risks, impacts, risk levels and occupational safety and health (OHS) controls in the physics and chemistry laboratories of the Occupational Safety and Health Center (OHS) Medan. This is a qualitative research method with phenomenological approach hazard identification using Task Risk Analysis method using AS/NZS 4360: 2004 semi-quantitative. The tolerable risk threshold in the chemistry lab was 52, priority 3 was 10, and major was 11. The only thing OHS controlled in the physics lab was the air conditioning system. The presence of SOP (work procedures), MSDS (material safety data sheet) documents, OHS signs, supervision, managerial support, and the use of PPE masks, gloves, long-hand lab coats, rubber shoes, and other safety measures were all necessary in chemistry labs. Expanding the space, adding SOP, installing ventilation are all suggested at the physics laboratorium, Adopting ANSI / AIHA Z9.5-2003 ventilation guidelines, changing or replacing processes with safer chemicals, providing OHS training, and wearing coveralls and glasses are all recommended in the chemistry laboratory.